Effects of GLP-1 Receptor Agonists on Bone Mineral Density in Patients with Type 2 Diabetes Mellitus: A 52-Week Clinical Study. (18th September 2021) - Cai, Ting-ting; Li, Hui-qin; Jiang, Lan-lan; Wang, Hui-ying; Luo, Meng-hui; Su, Xiao-fei; Ma, Jian-hua
Abstract : Introduction . Hypoglycemic drugs affect the bone quality and the risk of fractures in patients with type 2 diabetes mellitus (T2DM). We aimed to investigate the effects of glucagon-like peptide-1 receptor agonists (GLP-1RAs) and insulin on bone mineral density (BMD) in T2DM. Methods . In this single-blinded study, a total of 65 patients with T2DM were randomly assigned into four groups for 52 weeks: the exenatide group (n = 19 ), dulaglutide group (n = 19 ), insulin glargine group (n = 10 ), and placebo (n = 17 ). General clinical data were collected, and BMD was measured by dual-energy X-ray absorptiometry. Results . Compared with baseline, the glycosylated hemoglobin (HbA1c) decreased significantly in the exenatide (8.11 ± 0.24 % vs. 7.40 ± 0.16 %, P = 0.007 ), dulaglutide (8.77 ± 0.37 % vs. 7.06 ± 0.28 %, P < 0.001 ), and insulin glargine (8.57 ± 0.24 % vs. 7.23 ± 0.25 %, P < 0.001 ) groups after treatment. In the exenatide group, the BMD of the total hip increased. In the dulaglutide group, only the BMD of the femoral neck decreased (P = 0.027 ), but the magnitude of decrease was less than that in the placebo group; the BMD of L1-L4, femoral neck, and total hip decreased significantly (P < 0.05 ) in the placebo group, while in the insulin glargine group, the BMD of L2, L4, and L1-4 increased (P < 0.05 ). Compared with the placebo group, the BMD of the femoral neck and total hip in the exenatide group and the insulin glargine group were increased significantly (P < 0.05 ); compared with the exenatide group, the BMD of L4 in the insulin glargine group was also increased (P = 0.001 ). Conclusions . Compared with the placebo, GLP-1RAs demonstrated an increase of BMD at multiple sites of the body after treatment, which may not exacerbate the consequences of bone fragility. Therefore, GLP-1RAs might be considered for patients with T2DM. This trial is registered with ClinicalTrials.gov NCT01648582 .